2022
DOI: 10.1186/s40170-022-00299-4
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil increases the antitumor activity of 5-FU through inhibiting PRMT5-mediated glycolysis and cell proliferation in colorectal cancer

Abstract: Background Protein arginine methyltransferase 5 (PRMT5) is upregulated in multiple tumors and plays a pivotal role in cancer cell proliferation. However, the role of PRMT5 in colorectal cancer remains poorly understood. Methods We detected the expression level of PRMT5 and glycolytic enzymes using online databases and colorectal cancer cell lines by immunohistochemical staining, quantitative real-time polymerase chain reaction (qRT-PCR), and wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…For instance, Olaparib-resistant ovarian adenocarcinoma cells and 5-FU resistant gastric cancer tissue both showed an increase in EHMT2 protein expression [ 39 , 40 ]. In addition, PRMT5 was found to be implicated in 5-FU resistance in CRC cells (HCT-116 and SW480 cell lines) in vitro and in vivo [ 41 ]. One exception in our results was found in one of the biological repeats of the 5-FU desensitized Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Olaparib-resistant ovarian adenocarcinoma cells and 5-FU resistant gastric cancer tissue both showed an increase in EHMT2 protein expression [ 39 , 40 ]. In addition, PRMT5 was found to be implicated in 5-FU resistance in CRC cells (HCT-116 and SW480 cell lines) in vitro and in vivo [ 41 ]. One exception in our results was found in one of the biological repeats of the 5-FU desensitized Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…PRMT5 plays a crucial role in intestinal diseases such as enteritis and colorectal cancer development (Hernandez et al, 2023;Yang and Bedford, 2013). Mechanistic studies have suggested that PRMT5 can promote colorectal cancer cell growth by transcriptionally silencing anti-oncogenes or/and activating oncogenes (Cho et al, 2012;Prabhu et al, 2015;Shen et al, 2022;Yan et al, 2021;Zhang et al, 2015). In IBD, upregulation of PRMT5 contributes to clearing Citrobacter rodentium infection and promoting mucosal damage recovery during enteric infection (Hernandez et al, 2023).…”
Section: Introductionmentioning
confidence: 99%